Postoperative analgesia using fentanyl plus celecoxib versus epidural anesthesia after laparoscopic colon resection - Yoshida, Tadashi; Homma, Shigenori; Shibasaki, Susumu; Shimokuni, Tatsushi; Sakihama, Hideyasu; Takahashi, Norihiko; Kawamura, Hideki; Taketomi, Akinobu (Surgery today (Tokyo, Japan), 2017)
Purpose Effective postoperative analgesia is essential to a patient’s recovery after laparoscopic colon resection (LCR). We introduce a new analgesic protocol using fentanyl plus celecoxib following LCR. Methods The subjects of this retrospective comparative study were 137 patients who underwent LCR, 63 of whom were treated with 72 h of epidural anesthesia (group E), and 74 of whom were treated with 24 h of fentanyl intravenous injection followed by 7 days of oral celecoxib (group FC). We evaluated the safety and efficacy of this new protocol. Results The combination of fentanyl and celecoxib maintained a low postoperative pain score (<1.5, evaluated by the FACES Pain Scale) and reduced the need for rescue analgesic drugs for 7 days (groups E vs. FC: 5.39 ± 3.77 vs. 2.79 ± 2.92, p < 0.001). The postoperative hospital stay was almost equal for the two groups (E vs. FC: 11.1 ± 4.5 vs. 10.3 ± 4.8 days, p = 0.315). The operating room stay other than for surgery was significantly shorter for group FC (E vs. FC: 128.7 ± 30.5 vs. 107.2 ± 17.0 min, p < 0.001). Neither group experienced complications, apart from one group FC patient, who suffered transient nausea and vertigo. Conclusions The new analgesic protocol using fentanyl plus celecoxib is an effective and time-saving strategy for LCR.